Pentingnya Pelajaran Pancasila Dan Kewarganegaraan Dalam Membentuk Karakter Dan Moral Siswa Di Sekolah - Agtania Yunisa Putri (Lembaga Pengembangan Kinerja Dosen, 2024)
Currently, Indonesia is facing a widespread crisis of national character and morals. This character crisis is very much dominated by the younger generation at school age. The role of Pancasila and citizenship lessons in schools is very important to shape the character and morals of students as the nation's successors so that they have quality and superior character in the future. The aim of this research is to find out the importance of Pancasila and citizenship lessons in shaping the character and morals of students at school. The method used in this article is the Systematic Literature Review (SLR) method, namely selecting each journal or previous research, then obtaining the results in the form of ideas that will be developed later. Pancasila and citizenship lessons (PKN) are one of the subjects in school where one of the aims is to shape the character of the nation's successors. It is hoped that character formation through the application of Pancasila values can lead students to grow and develop into citizens with character, morals, responsibility and remember their rights and responsibilities as Indonesian citizens. This research shows that Pancasila and citizenship lessons are very important and useful for students. Bad character and morals are certainly worrying for the development of student behavior, and vice versa, good character will give birth to the next generation with good character and morals.